Electrical equipment electrical AC and DC motors - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with basic concepts associated with the operation of electric motors. After completing this unit, trainees should be able to explain the basic principles of motor operation and describe the basic operation of a simple AC motor and a simple DC motor. They should also be able to identify and describe the function of each part of a typical AC motor and a typical DC motor.
Keywords: Electric motors -- Starting devices; Electric controllers